'Leaky' Bodies, Connectivity and Embodied Transitional Justice. (25th February 2019) - Clark, Janine Natalya
Abstract ∞ : Within the ever-growing field of transitional justice, it is striking that little attention has been given to bodies, except in the sense of what has been done to them. Seeking to address this gap by focusing on what bodies can do, this interdisciplinary article argues that bodies represent important sites of connectivity that can bring together communities fractured by war and armed conflict. In developing this thesis, it emphasizes how the leakiness of bodies – which has traditionally been viewed in negative terms – can help to foster a positive awareness of corporeal connectivity. Distinguishing between what it terms grounded and meta-functional connectivity, it calls for embodied ways of doing transitional justice that operationalize both types of connectivity. While the article is primarily a theoretical and conceptual piece, its empirical threads draw from the author's recent fieldwork with victims–survivors of conflict-related sexual violence in Bosnia and Herzegovina, Colombia and Uganda.